Longitudinal impact of preregistration interprofessional education on the attitudes and skills of health professionals during their early careers: a non-randomised trial with 4-year outcomes - Ben Darlow; Jennifer Roberts; Patrick McHugh; Melanie Brown; Eileen McKinlay; Peter Gallagher; Lesley Gray; Gordon Purdie; Christine Wilson; Sue Pullon; Louise Beckingsale; Kaye Cheetham; et al. (BMJ Open)
Objective To assess whether a preregistration interprofessional education (IPE) programme changed attitudes towards teamwork and team skills during health professionals’ final year of training and first 3 years of professional practice.Design Prospective, longitudinal, non-randomised trial.Setting Final year health professional training at three academic institutions in New Zealand.Participants Students from eight disciplines eligible to attend the IPE programme were recruited (617/730) prior to their final year of training. 130 participants attended the IPE programme; 115 intervention and 372 control participants were included in outcome analysis.Intervention The 5-week Tairāwhiti IPE (TIPE) immersion programme during which students experience clinical placements in interdisciplinary teams, complete collaborative tasks and live together in shared accommodation.Main outcome measures Data were collected via five surveys at 12-month intervals, containing Attitudes Towards Healthcare Teams Scale (ATHCTS), Team Skills Scale (TSS) and free-text items. Mixed-model analysis of covariance, adjusting for baseline characteristics, compared scores between groups at each time point. Template analysis identified themes in free-text data.Results Mean ATHCTS scores for TIPE participants were 1.4 (95% CI 0.6 to 2.3) points higher than non-TIPE participants (p=0.002); scores were 1.9 (95% CI 0.8 to 3.0) points higher at graduation and 1.1 (95% CI −0.1 to 2.4) points higher 3 years postgraduation. Mean TSS scores for TIPE participants were 1.7 (95% CI 0.0 to 3.3) points higher than non-TIPE participants (p=0.045); scores were 3.5 points (95% CI 1.5 to 5.5) higher at graduation and 1.3 (95%CI −0.8 to 3.5) points higher 3 years postgraduation. TIPE participants made substantially more free-text comments about benefits of interprofessional collaboration and perceived the TIPE programme had a meaningful influence on their readiness to work in teams and the way in which they performed their healthcare roles.Conclusions TIPE programme participation significantly improved attitudes towards healthcare teams and these changes were maintained over 4 years.